INFLUENCE OF GASEOUS MEDIA ON DAMPING OF PNEUMATIC COUPLINGS - Jozef KRAJŇÁK (Scientific Journal of Silesian University of Technology. Series Transport)
In our department has long been devoted specifically flexible pneumatic shaft couplings. These couplings are filled with a gaseous medium air. Examination, we found that the type of gas, its properties such as gas density, compressibility factor, molecular weight and viscosity alter dynamic properties pneumatic coupling. The main objective of this article is to determine how various gaseous media influences damping coefficient b. The article compares three different gases, air, helium and propane-butane. These gases have different properties and it can change damping coefficient b. The measurements are performed in the laboratories of our department in Košice. We used flexible one-bellow pneumatic coupling 4-1/70-T-C and two-bellows pneumatic coupling 4-2/70-T-C. Pressure gaseous medium was varied in the range of 100 to 600kPa.